Student perceptions of online homework in mathematics of accounting and finance - Sarmiento, Celina P. (Animo Repository, 2017)
Online homework, as an alternative to the traditional paper-pencil type, opens up many possibilities that can help students learn even when outside the school. It is an innovative system that offers many advantages, both for teachers and students. Thus, exploring its potentials and impact in different educational regime is in order. Accordingly, this paper presents the results of a study that investigated the use of online homework given through a free access system, MyOpenMath, which is optimized for mathematics subjects. A set of homework, structured to emulate immediate attempt-feedback-reattempt process, were developed and administered to Mathematics of Accounting and Finance students through the above-mentioned platform. A survey on 142 students determined their perceptions on the use of MyOpenMath, and an interview with selected respondents explained the outcome of the survey. Results indicated that regardless of gender, type of high school, mathematical performance, and computer attitude, students had a greatly positive perception towards online homework given through MyOpenMath. It appears that students appreciated the features of the said system, which motivated them and increased their confidence in answering homework. Students reported that taking online homework was a pleasant experience and that it helped them prepare for examinations. © 2017 American Scientific Publishers All rights reserved.